2022
DOI: 10.1175/jtech-d-21-0169.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of a Commercial Broadband Echo Sounder for Remote Observations of Turbulent Mixing

Abstract: Stratified oceanic turbulence is strongly intermittent in time and space, and therefore generally under-resolved by currently available in situ observational approaches. A promising tool to at least partly overcome this constraint are broadband acoustic observations of turbulent microstructure that have the potential to provide mixing parameters at orders of magnitude higher resolution compared to conventional approaches. Here, we discuss the applicability, limitations, and measurement uncertainties of this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Features off Cape Hallet Peninsula gave a similar re ectivity to subglacial discharge measured from the nearby Tucker Glacier (Fig. S8) and to signals obtained from strati ed turbulences in other global regions [16][17][18] . We consistently found metazoan dead zones at the centre of uid seeps, with transition zones dominated by opportunistic mega-epifaunal taxa that were relatively rare in the surrounding biologically-rich area at these sites (Fig.…”
supporting
confidence: 54%
“…Features off Cape Hallet Peninsula gave a similar re ectivity to subglacial discharge measured from the nearby Tucker Glacier (Fig. S8) and to signals obtained from strati ed turbulences in other global regions [16][17][18] . We consistently found metazoan dead zones at the centre of uid seeps, with transition zones dominated by opportunistic mega-epifaunal taxa that were relatively rare in the surrounding biologically-rich area at these sites (Fig.…”
supporting
confidence: 54%
“…Muchowski et al. (2022) showed that in areas where biological scattering does not dominate the signal, turbulent microstructure is the primary source of acoustic backscatter recorded with the R/V Electra EK80 system in this region and time of year. In this study, real‐time acoustic observations enabled us to plan positions of the MSS measurements and to target local mixing hotspots.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…While the MSS profiler measures small‐scale turbulent velocity fluctuations, the EK80 measures acoustic backscatter from density and sound speed fluctuations, caused by temperature and salinity fluctuations (e.g., Lavery et al., 2013). Therefore, acoustics only register turbulent structures in regions with existing background temperature and salinity gradients, where turbulent stirring induces temperature and salinity microstructure and thus increased acoustic backscatter (Muchowski et al., 2022). In contrast, MSS measurements show dissipation rates also in well‐mixed parts of the water column.…”
Section: Study Area and Methodsmentioning
confidence: 99%